The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1111/j.1476-5381.1980.tb07889.x
|View full text |Cite
|
Sign up to set email alerts
|

An Electrophysiological Analysis of the Effects of Morphine on the Calcium Dependence of Neuromuscular Transmission in the Mouse Vas Deferens

Abstract: 1 The effects of morphine on the Ca-dependence of the synaptic potential amplitude in the mouse vas deferens have been determined.2 The synaptic potential increased with a power factor of 2.4 for [Ca]. between 0.7 mm and 1.8 mm.Morphine (40 nM) decreased the synaptic potential, without altering the second power relationship between the synaptic potential and [Ca]0. 3 Morphine reversed the depression in the synaptic potential which develops during a short highfrequency (10 Hz) train of impulses to facilitation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 41 publications
5
28
0
Order By: Relevance
“…Addition of The 2.4 power relationship between [Ca]. and noradrenaline release observed in these studies confirms the findings of others (Bennett & Florin, 1975;Bennett & Lavidis, 1980;Milner et al, 1982) and possi- (Bennett & Florin, 1975) using the mass action law derived by Jenkinson (1957 mesenteric ganglion (Bornstein & Fields, 1979) nor with morphine; (0) chronic morphine-treated (CMT) in the smooth muscle cells of vasa deferentia (North (Bennett & Lavidis, 1980;Illes etal., 1980). These possibilities are supported by the finding that acute administration of morphine in mice and rats decreases Ca2+ levels in synaptosomes and in synaptic vesicles (Harris et al, 1977;Yamamoto et al, 1978).…”
Section: Depression In Transmitter Releasefrom Vasa Deferentia Oftolesupporting
confidence: 86%
See 4 more Smart Citations
“…Addition of The 2.4 power relationship between [Ca]. and noradrenaline release observed in these studies confirms the findings of others (Bennett & Florin, 1975;Bennett & Lavidis, 1980;Milner et al, 1982) and possi- (Bennett & Florin, 1975) using the mass action law derived by Jenkinson (1957 mesenteric ganglion (Bornstein & Fields, 1979) nor with morphine; (0) chronic morphine-treated (CMT) in the smooth muscle cells of vasa deferentia (North (Bennett & Lavidis, 1980;Illes etal., 1980). These possibilities are supported by the finding that acute administration of morphine in mice and rats decreases Ca2+ levels in synaptosomes and in synaptic vesicles (Harris et al, 1977;Yamamoto et al, 1978).…”
Section: Depression In Transmitter Releasefrom Vasa Deferentia Oftolesupporting
confidence: 86%
“…Facilitation oftransmifer release during lowfrequency stimulation in vasa deferentia from tolerant mice During a low frequency train of impulses the amount of transmitter released by successive impulses has been shown to be facilitated, and the degree of facilitation is calcium-dependent (Bennett & Fisher, 1977;Bennett & Lavidis, 1980). Smith & Zucker (1980) have shown that there is no facilitation of the entry of calcium into the terminal during a train of impulses but there is a prolonged rise in the internal calcium concentration.…”
Section: Depression In Transmitter Releasefrom Vasa Deferentia Oftolementioning
confidence: 99%
See 3 more Smart Citations